2007
DOI: 10.1039/b613672a
|View full text |Cite
|
Sign up to set email alerts
|

Template synthesis of benzannulated triphosphacyclononanes—a new class of phosphacrowns via template assisted nucleophilic P–C bond formation

Abstract: A 9-membered triphosphorus macrocycle with o-phenylene backbone functions has been stereoselectively prepared on a CpFe(+) template by two successive nucleophilic attacks of coordinated phosphide on a coordinated o-fluorophenylbiphosphine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 27 publications
3
41
0
Order By: Relevance
“…A similar reaction has been described with [Fe(η 5 -C 5 H 5 )(η 6 -PhMe)]PF 6 and a related diphosphane. [10] Complex [3]PF 6 was not isolated but instead was directly treated with 1 equiv. of 2-azidoethyl isocyanide (4) [11] in dichloromethane to give complex [5] The signal for the isocyanide carbon atom (C-16) in the 13 C{ 1 H} NMR spectrum of [3]PF 6 appears at δ = 164.2 ppm with a 2 J(P,C) coupling constant of 28.0 Hz.…”
Section: Resultsmentioning
confidence: 99%
“…A similar reaction has been described with [Fe(η 5 -C 5 H 5 )(η 6 -PhMe)]PF 6 and a related diphosphane. [10] Complex [3]PF 6 was not isolated but instead was directly treated with 1 equiv. of 2-azidoethyl isocyanide (4) [11] in dichloromethane to give complex [5] The signal for the isocyanide carbon atom (C-16) in the 13 C{ 1 H} NMR spectrum of [3]PF 6 appears at δ = 164.2 ppm with a 2 J(P,C) coupling constant of 28.0 Hz.…”
Section: Resultsmentioning
confidence: 99%
“…The coupling of the phosphine ligands of [(h 5 -C 5 H 5 )-Fe{kP,kP-(C 6 H 4 F-2) 2 PCH 2 CH 2 P(C 6 H 4 F-2) 2 }(PH 2 Ph)]PF 6 (9) was achieved by addition of base (Scheme 15) [68]. Photolysis of [(h 5 -C 5 H 5 )Fe(h 6 -C 6 H 4 Me 2 -1,4)]PF 6 in the presence of (C 6 H 4 F-2) 2 PCH 2 CH 2 P(C 6 H 4 F-2) 2 in acetonitrile, followed by treatment with PhPH 2 at elevated temperature gave the salt 9, which on treatment with two equivalents of KOBu t in THF gave salt 10 in an overall yield of 75% (with respect to [(h 5 -C 5 H 5 )Fe(h 6 -C 6 H 4 Me 2 -1,4)]PF 6 ).…”
Section: Intramolecular C-f Bond Cleavagementioning
confidence: 99%
“…No metal complexes of the ligand were reported but the methyl iodide salt [9] The majority of the reports related to [9]aneP 3 type cyclononane ligands has arisen from one group, much of the chemistry utilising the activated, electrophilic ortho-fluorophenyl substituent on a neighbouring pnictide donor [288][289][290][291][292][293][294][295][296][297][298][299].…”
Section: Synthesismentioning
confidence: 99%
“…The structure of the complex shows the facial coordination of the [9]aneP 3 ligand [295]. In neither of these reports was the ligand isolated in its free form [295,296] [292]. The authors reported that attempts to displace the macrocycle from the complex with chelating agents such as ethylenediaminetetraacetic acid, and cyanide ion were not successful [292].…”
Section: Syntheses and Properties Of Metal Complexesmentioning
confidence: 99%